Economic Empowerment of Haor Women through Duck Farming in Bangladesh (The Agriculturists, 2016)
A study was conducted to investigate the extent of women participation in duck rearing farm and to address womens economic empowerment in Hakaluki haor area of Maulvibazar district in Bangladesh. Primary data from 80 women duck raisers were collected through face to face interview. In this case haor women played an important role in the duck rearing activities which were carried out to explore the meaningful interpretation of womens present status. The result of the study revealed that duck rearing farming has exerted greater impact on improving socioeconomic condition and economic empowerment of haor women. The successful duck farming provides the women with economic independence and improved livelihood leading to their empowerment.The Agriculturists 2015; 13(1) 18-25